If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 2 + 8x + 2x Combine like terms: 8x + 2x = 10x 2 = 2 + 10x Add '-2' to each side of the equation. 2 + -2 = 2 + -2 + 10x Combine like terms: 2 + -2 = 0 0 = 2 + -2 + 10x Combine like terms: 2 + -2 = 0 0 = 0 + 10x 0 = 10x Solving 0 = 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 0 + -10x = 10x + -10x Remove the zero: -10x = 10x + -10x Combine like terms: 10x + -10x = 0 -10x = 0 Divide each side by '-10'. x = 0 Simplifying x = 0
| =-9(1+m)-2m | | 9-3(0)/-5 | | =9(8k+2) | | 19x-5=14x-30 | | 3(4x+6)+2(6x+4)+3=24x+30 | | 3/2-1/4= | | =2(p+5) | | =5(3x+3) | | =-3(9+4a) | | 16x^2+62x-45=0 | | =-5x-8+10-7x | | 15x-9=2x+8 | | =-5v+v | | 2/8x+16= | | 5(x-1)+8(x-6)=180 | | 13.310=.25(x-70000)+9735 | | =7+9b-6 | | 4xsquar-5x-6=0 | | 3x^3=3x(x+30) | | 28=6(u+4)-8u | | x+7/7+x= | | 4(-3n+7)-3n=118 | | 6(180-x)-5=x | | 11.3+-7.2f=-3.82 | | 48t+265=553 | | 5x+3=14x-42 | | F(x)=x^2-3x-4/x^2-25 | | 2x+2x+x+9+x+9=84 | | =3-4n+9 | | w-0.06w=26.32 | | [5-2x]+3=8 | | 3-3x=27 |